An overview of directivity control methods of the parametric array loudspeaker - Shi, Chuang (2016)
A sound reproduction system usually consists of several types of loudspeakers to cater to sophisticated applications. The directivity of a loudspeaker is a measure of its efficiency in sending sounds to a particular direction instead of all directions. Demand to control the directivity of a sound reproduction system is gaining momentum with many new designs of directional loudspeakers, including the acoustic dome, horn loudspeaker, loudspeaker array, and parametric array loudspeaker (PAL). The PAL is an application of the parametric acoustic array in air, which generates a sound beam from the interaction of ultrasonic beams. The PAL has several desired features, such as its narrow beamwidth over a wide frequency range, low sound attenuation over a long distance, and ability to reproduce perceptually near sound images. The PAL is also advantageous in using a smaller driving unit to transmit an equally narrow sound beam as compared to the conventional loudspeaker and broadside loudspeaker array. An overview of directivity control methods of the PAL is presented in this paper. In particular, acoustic models and signal processing techniques in controlling the directivity of the PAL are emphasized.